2016
DOI: 10.1371/journal.pone.0159273
|View full text |Cite
|
Sign up to set email alerts
|

What Matters Most for Predicting Survival? A Multinational Population-Based Cohort Study

Abstract: Despite myriad efforts among social scientists, epidemiologists, and clinicians to identify variables with strong linkages to mortality, few researchers have evaluated statistically the relative strength of a comprehensive set of predictors of survival. Here, we determine the strongest predictors of five-year mortality in four national, prospective studies of older adults. We analyze nationally representative surveys of older adults in four countries with similar levels of life expectancy: England (n = 6113, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
31
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 19 publications
2
31
0
2
Order By: Relevance
“…Furthermore, our sensitivity analyses supported our conclusions and minimize the possibility that these proxy substitutions markedly influenced the overall study findings. The factors used to assess LE in this index have been found to be predictive of mortality in multiple studies, suggesting that individuals in our population with functional and mobility limitations and comorbidities have a shorter LE than those without these conditions …”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Furthermore, our sensitivity analyses supported our conclusions and minimize the possibility that these proxy substitutions markedly influenced the overall study findings. The factors used to assess LE in this index have been found to be predictive of mortality in multiple studies, suggesting that individuals in our population with functional and mobility limitations and comorbidities have a shorter LE than those without these conditions …”
Section: Discussionmentioning
confidence: 88%
“…The factors used to assess LE in this index have been found to be predictive of mortality in multiple studies, suggesting that individuals in our population with functional and mobility limitations and comorbidities have a shorter LE than those without these conditions. 22,23 We did not have data on whether the tests were conducted for screening or diagnostic purposes, but it is recommended to use FOBT only for screening, and it is unlikely to be used for diagnostic purposes. A previous study that was able to distinguish between diagnostic and screening mammograms found that only approximately 15% of all mammograms were diagnostic.…”
Section: Discussionmentioning
confidence: 99%
“…Additional bias may be introduced by unobserved covariates that influenced the Veteran's decision to reside in MFH or CNH. For example, functional status is highly correlated with survival and was not included in this analysis because of limited availability . However, we have included multiple measures of illness severity to capture clinical differences between the groups of Veterans utilizing MFH and CNH.…”
Section: Discussionmentioning
confidence: 99%
“…For example, functional status is highly correlated with survival and was not included in this analysis because of limited availability. [43][44][45] However, we have included multiple measures of illness severity to capture clinical differences between the groups of Veterans utilizing MFH and CNH. Because these measures are highly correlated with functional status, we expect that functional status would also be similar across the two groups.…”
Section: Imputation Of Missing Potential Outcomesmentioning
confidence: 99%
“…However, our index also includes whether older adults need help with household chores, past cigarette use, perceived health, and hospitalizations in the past year. In a recent review of the top predictors of 5‐year mortality in four countries, age, sex, limitations in instrumental activities of daily living, mobility, and perceived health were all found to be top predictors and all of these variables are in our index . While there have been no direct comparisons of the performance of our index with other methods for estimating older adults prognosis; Pollack et al found that there was 84.9% agreement in categorization of Medicare beneficiaries as having <50% chance of survival in 9–10 years when our index, the Lee index, and a method for estimating life expectancy that uses US life table data while accounting for individuals' comorbidity were compared.…”
mentioning
confidence: 81%